2010
DOI: 10.4049/jimmunol.1000665
|View full text |Cite
|
Sign up to set email alerts
|

Kit Ligand and Il7 Differentially Regulate Peyer’s Patch and Lymph Node Development

Abstract: Hematopoietic lymphoid tissue inducer (LTi) cells initiate lymph node (LN) and Peyer’s patch (PP) development during fetal life by inducing the differentiation of mesenchymal organizer cells. The growth factor signals underlying LTi cell development and LN and PP organogenesis remain poorly understood. LTi cells express the Il7r and the receptor tyrosine kinase Kit, whereas organizer cells express their cognate ligands. To determine the relative significance of Il7 and Kit signaling in LTi cell homeostasis and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
43
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 42 publications
1
43
0
Order By: Relevance
“…Finally, our data suggest that Flt3L and IL-7 act on different stages of ILC development. The development of LNs and PPs depends on LTi cells (7) and is regulated by cytokines such as IL-7, SCF, and receptor activator of NF-kB ligand (29,(53)(54)(55) mice. In contrast, the lack of PPs is presumably caused by the simultaneous reduction of both LTin and LTi cell numbers in the SI of flt3l 2/2 mice.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, our data suggest that Flt3L and IL-7 act on different stages of ILC development. The development of LNs and PPs depends on LTi cells (7) and is regulated by cytokines such as IL-7, SCF, and receptor activator of NF-kB ligand (29,(53)(54)(55) mice. In contrast, the lack of PPs is presumably caused by the simultaneous reduction of both LTin and LTi cell numbers in the SI of flt3l 2/2 mice.…”
Section: Discussionmentioning
confidence: 99%
“…1A). We have previously shown that IL-7 is crucial for LTi cell (45) and LN development (31) and that, in addition to IL-7, other cytokines promote intestinal LTi cell and PP development (29,31). To investigate whether Flt3L has an influence on LTi cell development, we analyzed fetal and neonatal flt3l 2/2 mice and compared them with WT and Il7 2/2 mice.…”
Section: Flt3l Regulates Intestinal Lti Cell Numbers and Pp Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition there are differences in essential transcription factors which are necessary to develop lymph nodes or PP, like interleukin (IL) 7 and RANK (Chappaz, Gartner et al 2010). Using mice deficient for IL7 or Kit or both they showed that IL7 is important for lymph node anlagen but not for PP development whereas both Kit and Il7 are important for MLN anlagen (Chappaz, Gartner et al 2010). But growth factors needed for lymph node development still remain poorly understood.…”
Section: Lymph Node Formationmentioning
confidence: 99%
“…Although LNs and PPs differ in their molecular requirements for initiating organogenesis, LTab and LTi cells that express LTab are key components regulating anlage formation, the former at the molecular level and the latter at the cellular level (13)(14)(15)(16)(17). LTi cells diverge from the lymphocyte differentiation pathway in the fetal liver (15,18), and two transcriptional regulators, Id2 and RORg, have been identified as essential for the lineage commitment of LTi cells (19)(20)(21)(22)(23).…”
mentioning
confidence: 99%